About Your Child's Eating (AYCE) scale psychometrics when applied to children in hospital-based feeding clinics. Issue 4 (2nd October 2018) - Hendy, Helen M.; Seiverling, Laura J.; Williams, Keith E.; Mazzeo, Debra; Harclerode, Whitney
ABSTRACT: This study examined the About Your Child's Eating scale (AYCE) when applied to a sample of children referred to hospital-based feeding clinics. The AYCE measures three dimensions of the family mealtime environment (Child Resistance to Eating, Positive Mealtime Environment, Parent/Caregiver Mealtime Aversion). Confirmatory factor analysis for AYCE subscales revealed close to acceptable goodness-of-fit values, strong internal reliability, and strong test-retest reliability. ANCOVAs examining AYCE subscales and child demographics found caregivers of younger and thinner children reported more Child Resistance to Eating and Caregiver Aversion to Mealtime, with other demographics not statistically significant.